Indução magnética: energia evolucionária - SILVA, Gabriel Souza (2022)
This paper discusses the study on how the induction heating system has been established within a social environment, where the use of traditional methods, which still prevails, in food preparation and among other activities. The use of induction stoves as described in this study shows an important part of history, which over the years has had numerous contributions from several scholars enabling what we have today in relation to the evolution of technologies that allow us a better performance related to time and practicality. The induction cooker as object of study, an information was made with relevance so that we can make a more complete analysis addressing its physical characteristics, operating mode, energy matrices and also its comparison with the heating system of gas stoves.